Conflict and Culture: Shaping Civilization through Dialogue and Transformation - Arditya Prayogi; Dimas Prasetya; Ryan Marina; Singgih Setiawan; Ishak, Muhammad Isyraf (Interdisciplinary Journal of Social Sciences, 2025)
Conflict and culture are two inseparable elements in the history of human civilization. Throughout history, conflict has often emerged as a result of differences in values, ideologies, and interests, but culture has often been a bridge that has made peace possible. This study aims to explore the relationship between conflict and culture, and to analyze how culture can act as a tool for transforming conflict into sustainable peace. The method used in this writing is qualitative analysis with a historical and sociological approach. Data were collected from various academic literature, case studies, and relevant historical documents. The results of the writing show that culture has an important role in creating cross-group understanding, building dialogue, and creating empathy. Elements such as art, tradition, language, and universal values ​​are often effective media in reducing tensions. Case studies of conflicts in various regions show that culture-based initiatives, such as cultural diplomacy, collective art, and cross-cultural education programs, have a positive impact on reducing conflict and building peace. The implication of this research is the need to strengthen the role of culture in diplomacy and conflict resolution efforts. Global policies that are more oriented towards cultural dialogue can be a key strategy for creating harmony amidst diversity.